Abiotic Stress-Related Expressed Sequence Tags from the Diploid Strawberry Fragaria vesca f. semperflorens - Rivarola, Maximo Lisandro (2011)
Strawberry (Fragaria spp.) is a eudicotyledonous plant that belongs to the Rosaceae family, which includes other agronomically important plants such as raspberry (Rubus idaeus L.) and several tree-fruit species. Despite the vital role played by cultivated strawberry in agriculture, few stress- related gene expression characterizations of this crop are available. To increase the diversity of available Fragaria transcriptome sequence, we produced 41,430 Fragaria vesca L. expressed sequence tags (ESTs) from plants growing under water-, temperature-, and osmotic-stress conditions as well as a combination of heat and osmotic stresses that is often found in irrigated fi elds. Clustering and assembling of the ESTs resulted in a total of 11,836 contigs and singletons that were annotated using Gene Ontology (GO) terms. Furthermore, over 1200 sequences with no match to available Rosaceae ESTs were found, including six that were assigned the ?response to stress? GO category. Analysis of EST frequency provided an estimate of steady state transcript levels, with 91 sequences sequences exhibiting at least a 20-fold difference between treatments. This EST collection represents a useful resource to advance our understanding of the abiotic stress-response mechanisms in strawberry. The sequence information may be translated to valuable tree crops in the Rosaceae family, where whole-plant treatments are not as simple or practical.